High-resolution genetic analysis of whole APC gene deletions: a report of two cases and patient characteristics - Hiroki Tanabe; Yasuyuki Koshizuka; Kazuyuki Tanaka; Kenji Takahashi; Masami Ijiri; Keitaro Takahashi; Katsuyoshi Ando; Nobuhiro Ueno; Shin Kashima; Takeo Sarashina; Kentaro Moriichi; Kenrokuro Mitsube; et al. (Human Genome Variation)
Abstract Familial adenomatous polyposis (FAP) is an autosomal dominant syndrome caused by germline variants in the APC gene, leading to the development of numerous colorectal polyps and significantly increases the risk of colorectal cancer. A diagnosis is typically made using colonoscopy, and genetic testing can assist in patient surveillance and carrier identification. Recent advances include the use of whole-genome array comparative genomic hybridization (a-CGH), which provides better resolution of genetic imbalances. We aimed to explore the specific features of FAP patients with whole APC gene deletions using high-resolution a-CGH and to compare patient characteristics. Two polyposis patients with whole APC deletions were identified, and the lost genetic sizes ranged from 0.3–1.1 Mb. Nervous abnormalities were a characteristic symptom in a patient with a 1.1 Mb loss. A patient with an approximately 0.3 Mb loss, which included the entire APC gene, presented a polyposis phenotype without intellectual disability. The comparison of genetic losses, with or without intellectual disability, revealed 7 genetic changes. Consequently, EPB41L4A is a candidate gene associated with the neurogenic phenotype.